Strategic value contribution through speed in procurement - A capability microfoundation perspective - Aminoff, Anna; Lorentz, Harri; Kaipia, Riikka (Elsevier, 2026)
In rapidly changing business environments, speed emerges as a pivotal catalyst for enhanced procurement performance and value creation. The literature, however, lacks a comprehensive conceptual treatment of speed, particularly in the procurement context. To better understand how procurement can be accelerated for improved value contribution, we explored the associated capability microfoundations. Drawing on the literature and utilising a multiple case study approach (involving 14 companies) complemented by workshops, three distinct types of speed were confirmed and elaborated upon: operating speed, strategic adaptation speed, and response speed. Further, in the context of these speed types, we gained theoretical insights into procurement acceleration. We also identified a range of microfoundations across the categories of structures, processes, technologies, and individuals, encompassing established practices such as early involvement, (de)centralisation, and use of data and analytics. We also made theoretically interesting observations on the business-driven organising of procurement for aligning with the required clock-speed, agile teams and ways of working for quick problem-solving, and organisational structures that reduce throughput time. Regarding future research, new structural and process variants must be explored from the perspectives of speed and acceleration, while recognising the dangers of the self-inflicted pathology in terms of unbridled acceleration in the face of a perceived need to survive.